2012
DOI: 10.1107/s090904951200235x
|View full text |Cite
|
Sign up to set email alerts
|

Micrometre resolution of a charge integrating microstrip detector with single photon sensitivity

Abstract: A synchrotron beam has been used to test the spatial resolution of a singlephoton-resolving integrating readout-chip coupled to a 320 mm-thick silicon strip sensor with a dedicated readout system. Charge interpolation methods have yielded a spatial resolution of x ' 1.8 mm for a 20 mm-pitch strip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…In one dimension, the non-uniform charge sharing is corrected analytically by using the so-called -algorithm described by Belau et al (1983), as shown by Schubert et al (2012). A similar approach has been used by Cartier et al (2014) using MÖ NCH by analyzing separately the two Cartesian coordinates ð x ; y Þ.…”
Section: Position Interpolation Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In one dimension, the non-uniform charge sharing is corrected analytically by using the so-called -algorithm described by Belau et al (1983), as shown by Schubert et al (2012). A similar approach has been used by Cartier et al (2014) using MÖ NCH by analyzing separately the two Cartesian coordinates ð x ; y Þ.…”
Section: Position Interpolation Algorithmmentioning
confidence: 99%
“…Moreover, the low noise, together with the large amount of charge sharing, permits the absorption position of the photons to be estimated with sub-pixel resolution using interpolation (Schubert et al, 2012). The micrometer-level spatial resolution makes MÖ NCH ideal for high-resolution imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…5 shows the pixel on the sensor for Pilatus, Eiger and Mö nch. Similar to CCDs for soft X-rays it allows the determination of the absorption position of isolated photons with a resolution of 1-2 mm (Schubert et al, 2012).…”
Section: Hybrid Pixel Detectors With Smaller Pixelsmentioning
confidence: 99%
“…Although hybrid pixel detectors in photon-counting or integrating mode are excellent candidates to achieve high sensitivity and noise-free operation, reducing the pixel size is challenging due to the intrinsic spatial resolution limitations of the X-ray sensors (Dinapoli et al, 2014). Reaching good spatial resolution and very small pixels is far from trivial and involves a certain level of signal processing for photon position refinement (Schubert et al, 2012). In addition, keeping acceptable photon detection rates would require implementing part of the processing logic inside the pixel electronics.…”
Section: Detection Challenges For the Esrf Upgradementioning
confidence: 99%